Characterization of a double‐hit murine model of acute respiratory distress syndrome. (October 2014) - Voelker, Maria Theresa; Fichtner, Falk; Kasper, Michael; Kamprad, Manja; Sack, Ulrich; Kaisers, Udo X; Laudi, Sven
Summary The aim of the present study was to characterize a murine model of acute respiratory distress syndrome (ARDS) abiding by the Berlin definition of human ARDS and guidelines for animal models of ARDS. To this end, C57BL/6NCrl mice were challenged with lipopolysaccharide (LPS; 15 mg/kg, i.p.) followed 18 h later by injection of oleic acid (OA; 0.12 mL/kg, i.v.). Controls received saline injection at both time points. Haemodynamics were monitored continuously. Arterial blood gas analyses were performed just before and every 30 min after OA challenge. Ninety minutes after OA challenge, the chest of mice was scanned using micro‐computed tomography (CT). Cytokine concentrations were measured in plasma samples. Lungs were harvested 90 min after OA challenge for histology, immunohistochemistry, lung weight measurements and tissue cytokine detection. A histological lung injury score was determined. Eighteen hours after LPS challenge, mice exhibited a severe systemic inflammatory response syndrome. Oxygenation declined significantly after OA injections (Pao2/Fio2 283 ± 73 and 256 ± 71 mmHg at 60 and 90 min, respectively; P < 0.001). Bilateral patchy infiltrates were present on the micro‐CT scans. Histology revealed parenchymal damage with accumulation of polymorphonuclear neutrophils, intra‐alveolar proteinacous debris and few hyaline membranes. The lung wet : dry ratio indicated damage to the alveolar capillary membrane. Cytokine patterns evidenced a severe local and systemic inflammatory state in plasma and lung tissue. In conclusion, the described two‐hit model of ARDS shows a pathological picture of ARDS closely mimicking human ARDS according to the Berlin definition and may facilitate interpretation of prospective experimental results.